Development of plant based nanoemulsion and its application as natural preservative having antioxidant and antimicrobial properties to deliver active compounds in apple juice (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
In this study, active compound loaded stable nanoemulsion (surface charge -18 mV) was developed having small diameter (